Impact of extreme flooding on the annual survival of a riparian predator, the Brown Dipper Cinclus pallasii. (16th March 2013) - Chiu, Ming‐Chih; Kuo, Mei‐Hwa; Hong, Shiao‐Yu; Sun, Yuan‐Hsun; Sergio, Fabrizio
<x xml:space="preserve">Abstract</x> The predicted effects of global climate change include altered patterns of precipitation and more extreme weather events, leading to an increase in the severity and frequency of episodic disturbances such as floods. These changes may affect lotic prey communities, which could indirectly affect aquatic and riparian predators through trophic linkages. We assessed whether extreme flooding affected the apparent survival of Brown Dippers Cinclus pallasii in Taiwan using mark–resighting data and climate data. The probability of survival was negatively correlated with the degree of flooding, and survival of first‐year birds was lower than that of adults. Previous analyses of this system suggest that the main, indirect mechanism driving such patterns is the impact of flood disturbance on the aquatic invertebrate prey of Brown Dippers. Our results show that changes in prey communities induced by flooding have the potential to affect predators in aquatic and adjacent riparian habitats. This highlights the importance of considering cross‐ecosystem linkages when identifying conservation and management goals in the face of future climate uncertainty.